Potential Development of Friendly Tourism Muslim in North Sumatera Province - Tetty Yuliaty; Sri Sudiarti (Universitas Muslim Indonesia, 2022)
The tourism sector is very important for a country's economy because this sector has a large potential income for the community. However, the economic sector is currently experiencing a crisis due to the impact of Covid-19. Over the past eight months, the number of arrivals of domestic and foreign tourists to Indonesia has dropped dramatically, creating an unexpected crisis. This research aims to be able to help develop the business potential of Muslim Friendly Tourism in North Sumatra Province. Data collection methods by interview and documentation study. In fulfilling the validity of this research data triangulation was carried out with the source. Data analysis technique. This research is a descriptive study, with more descriptive characteristics from the results of interviews and documentation studies. that has been obtained will be analyzed qualitatively and described in descriptive form. The data analysis technique used in this study is to use data steps such as the data collection. Reduction, Data Display and Verification and Confirmation of Conclusions. The results of this study indicate that North Sumatra Province with the largest number of Muslims has very significant potential, especially since there are many new tourism objects which are very attractive potential. Moreover, there are many places of Islamic historical heritage and culinary places that are quite famous and halal. However, the problem of halal certification needs to be fixed, many products and services are not certified yet.